The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1088/0264-9381/28/6/065001
|View full text |Cite
|
Sign up to set email alerts
|

Linearized gravity and gauge conditions

Abstract: In this paper we consider the field equations for linearized gravity and other integer spin fields on the Kerr spacetime, and more generally on spacetimes of Petrov type D. We give a derivation, using the GHP formalism, of decoupled field equations for the linearized Weyl scalars for all spin weights and identify the gauge source functions occuring in these. For the spin weight 0 Weyl scalar, imposing a generalized harmonic coordinate gauge yields a generalization of the Regge-Wheeler equation. Specializing to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 49 publications
0
69
0
Order By: Relevance
“…In the a = 0 case, the middle component of the Maxwell field, φ 0 , satisfies the Fackerell-Ipser equation [16], and, the middle component of the linearised curvature satisfies a very similar equation [1]. In addition, the extreme components for both the Maxwell and linearised Einstein equations also satisfy second-order PDEs, known as the Teukolsky equations [27].…”
Section: Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the a = 0 case, the middle component of the Maxwell field, φ 0 , satisfies the Fackerell-Ipser equation [16], and, the middle component of the linearised curvature satisfies a very similar equation [1]. In addition, the extreme components for both the Maxwell and linearised Einstein equations also satisfy second-order PDEs, known as the Teukolsky equations [27].…”
Section: Previous Resultsmentioning
confidence: 99%
“…Recall that we consider the exterior region of the Kerr space-time, which is a manifold parameterised by (t, r, ω) ∈ R × (r + , ∞) × S 2 with the metric given in equation (1). As is well known [18], this can be uniquely extended to a maximal analytic extension, which, in turn, has a C 0 conformal compactification.…”
Section: 2mentioning
confidence: 99%
“…acting on type {b = p/2, s = p/2} GHP quantities, and the corresponding modified wave operator [6,1] T p := g αβ D α D β (2.2) (note that T 0 = ). Define the 2-forms…”
Section: Review Of the 4-dimensional Casementioning
confidence: 99%
“…Note that the usual D'Alembertian is included in T 2b , since T 0 = = g αβ ∇ α ∇ β . The operator T 2b for the 4-dimensional Teukolsky equations on the Kerr spacetime was found in [6]; see also [1] for the treatment of all vacuum type D solutions. Introducing certain "potentials" 2 for the spin-s fields, one can formulate the left hand side of (1.1) in terms of self-adjoint operators, and then following Wald's adjoint operator technique (introduced in [33]), it is possible to take the adjoint identity and reconstruct solutions of the field equations from solutions of the scalar equations; this way, stability questions can be approached by the study of a scalar, wave-like equation instead of the more complex tensor field equations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these are secondorder equations, and, when put in the form (∂ α L αβ (s)∂ β + W (s))(φ ±s ) = 0, the matrix of coefficients L is not symmetric, which prevents most of the standard tools of hyperbolic PDE from being applied. The middle Maxwell component φ 0 satisfies the equation [16] (∇ α ∇ α + 2M/p 3 )(pφ 0 ) = 0 with p = r + ia cos θ, and it has recently been shown that, for the linearised Einstein equation (in an appropriate gauge) [17], (∇ α ∇ α + 8M/p 3 )(p 2 φ 0 ) = 0. All of these equations can be separated.…”
Section: More Complicated Examplesmentioning
confidence: 99%